The Usage and the Need for Library Usage of Students and Lecturers in Souphanouvong University of Lao People’s Democratic Republic - SENGALOUN , Deng (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The aim of this research is to study the usage, problems of usage and the need of usage of Souphanouvong University’s Library. The research methodology was survey research by using the questionnaires, the quantitative are data studies collected from students and lectures affiliated at Souphanouvong University The samplings was in total 497 participants, and receive a 100% return questionnaire, the data were analyzed using the social science statistics to find the frequency, percentage, mean and standard deviation. The results showed that: 1) The usage of library service: the samplings student male 60.44% and professor males 65.40%. Mostly students had an aim to study and most of lecturers used library for reading books and academic documents. Moreover, students and lectures used library once a week. Mostly students and lectures used library during the free time of studying and teaching. Mostly students and lecturers found books by browsing bookshelves themselves. Moreover, both groups use books/text books the most, which for students and lecturers and mostly in Laotian use circulation service in middle level. 2) Problems of using library: 1) Library: most of students and lecturers commented that library had no copy machine. Information Resources; most of students and lecturers commented that Library resources are not enough in the high level. Technology; the server of computer network (OPAC) was slow in the medium level for searching were not enough in the medium level. Public Relation; both students and lecturers answered that the library did not have no Public Relation to inform the service of library which in the medium level. 2) Users: mostly answered that they did not had time to use library because library was closed during lunch time high level. 3) Service staffs; both students and lecturers answered that the numbers of service staff were not sufficient and effected to the service which was not enough in the medium level. 3) The need of library usage which were: all most of students and lecturers need the library to be cleaned and in good decoration in the high level, Information Resources: students need the journal in Laotian in every titles in high level and lecturers need references books (dictionary of Laotian) in high level. Library hours; students and lecturers both need library open during the lunch time in high level. Circulation Service: students and lecturers need to borrow thesis and research in high level. Information Service: students need Instruction Service in medium level and lecturers need guidance service in high level.